Child Protection in Criminal Offenses: An Analysis of Policies and Sanctions in the Indonesian Justice System - Udjari, Hendrianto; Hardyansah, Rommy; Darmawan, Didit; Mohamad, Yusran; Osean, Ricard (Judge : Jurnal Hukum, 2025)
This study examines the implementation of legal protection for children as perpetrators of criminal offenses in Indonesia's juvenile criminal justice system. The main focus of the study is to analyze the application of sanctions and protection provided to children involved in criminal acts, as well as evaluating the effectiveness of their rehabilitation and reintegration into society. The method used is Normative Juridical, with primary data analysis from relevant legislation and secondary data from related literature. The results show that there are large discrepancies between legal provisions and practices in the field, often resulting in a more punitive than restorative approach to child offenders. The research recommends policy reforms oriented towards education and psychological and social support, rather than just punishment.